(3GdeUGHjM aj GdMOjKs - (3CHh eMeO GdMSjf Hf eSYhO Hf eMeO GdaQGA GdHZhj GdTGaYj eMjj GdSfI,J (B516 (3g` s ((3CHh GdaVd Ydi Hf eMeO Hf fGUQ GdESaQGjjfi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdCLd eMi GdSfI fGbd GdMOjK Qcf GdESdGe CHh eMeO GdMSjf Hf eSYhO GdHZhi LYdJ CMGOjK cd HGH ef gPG GdcJGH Ydi bSejf UMGM hMSGf s
(3BNQgG (B:s
(3BNQg ef HGH KhGH gPg GdCeI (B: (3ef GdUMGM (B" (3bhdg (B" (3Yf CfS bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3eKd CeJi eKd GdeWQ dGjOQi Chdg NjQG Ce BNQg Je cJGH GdeUGHMj hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3hHYVgG HGdShGO eLhGOkG s
(3Ydi MhGTjgG JUMjMGJ hJYdjbGJ s
(3HChdgG hBNQgG SeGYGJ hbQGAGJ s
(3HYVgG bQGAI fGSN gPg GdfSNI SfI (B773 / (3hajgG PcQ eLGdS GdbQGAI s
Keywords: (3GdMOjK h GdeUWdMs